The shortcomings of employment as a durable solution - Bardelli, N (Refugee Studies Centre, University of Oxford, 2018)
The refugee assistance regime that prevails today seems to insist that the best, or only, solution to protracted refugee situations is firmly rooted in improving access to employment. This approach, however, inevitably favours some and excludes others, while also ignoring the deeper political and social issues at stake.